Pathogenicity and functional analysis of CFAP410 mutations causing cone-rod dystrophy with macular staphyloma - Yang, Shaoqing; Li, Ya; Yang, Lin; Guo, Qingge; You, Ya; Lei, Bo (Frontiers in Medicine, 2023)
Cone-rod dystrophy (CORD) caused by pathogenic variants in CFAP410 is a very rare disease. The mechanisms by which the variants caused the disease remained largely unknown. A 6-year-old boy complained decreased vision for 1 year, underwent ocular examinations together with systemic X-ray check. Blood sample was taken for targeted next generation sequencing (Tg-NGS). Pathogenicity of identified variants was determined by ACMG guideline. Mutated plasmids were constructed and transferred to HEK293T cells. Cell cycle, protein stability, and protein ubiquitination level was measured. The best-corrected visual acuity of proband was 0.20 bilaterally. Fundus showed macular staphyloma and uneven granular pigment disorder in the periphery of the retina. SS-OCT showed thinning and atrophy of the outer retina, residual ellipsoid zone (EZ) in the fovea. Scotopic and photopic ERG responses severe reduced. Two heterozygous missense pathogenic variants, c.319T >C (p.Tyr107His) and c.347C>T (p.Pro116Leu) in exon 4 of the CFAP410, were found and were pathogenic by the ACMG guideline. In vitro, pathogenic variants affect cell cycle. Immunofluorescence and western blotting showed that the mutant proteins decreased expression levels protein stability. Meanwhile, co-IP data suggested that ubiquitination level was altered in cells transferred with the mutated plasmids. Compound heterozygous pathogenic variants c.319T>C and c.347C>T in CFAP410 caused CORD with macular staphyloma. The pathogenic mechanisms may be associated with alternations of protein stability and degradation through the ubiquitin-proteasome pathway.